المرأة وقضاياها في أدب نجيب الكيلاني القصصي - Dr. Muhammad Saif ul Rahman (التراث الأدبي)
Najeeb Alkilani is considered the founder of Arabic Islamic literature and he believes that through Arabic Islamic Literature, it is a profound responsibility that flows through the veins of Muslim believers, stemming from their hearts and convictions. It is evident that delving into the life and literary works of this remarkable individual is a an obligation for researchers. This study aims to shed light on the significant contributions and literary impact of Doctor Najeeb Alkeelani, recognized as the founding figure of Arabic Islamic literature in contemporary Arabic literary circles, as well as his noteworthy efforts in addressing women's issues through his fictional works. The initial chapter of this research focuses on his life, while the subsequent chapter explores his portrayal of women and their challenges as depicted in his literature.